The Assisted Transformation of Models: Supporting Cyber-Physical Systems Design by Extracting Architectural Aspects and Operating Modes from Simulink Functional Models - Passarini, Rosane Fátima; Becker, Leandro Buss; Farines, Jean-Marie (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
The design process of Cyber-Physical Systems normally starts with the creation of funcional models that will be used for simulation purposes. However, most of the time such models are not directly reused for the design of the software architecture of the target embedded system. The present paper aims to fulfill this gap by introducing a novel mechanism called Assisted Transformation of models (AST) to transform typical functional (simulation) models designed in the Simulink environment into architectural models represented in the Architecture Analysis & Design Language (AADL). The use and benefits of the proposed mechanism are exemplified in the paper by means of a case study devoted for the design of an autonomous parking system.